Microscopy of Graphene Growth, Processing, and Properties. (11th April 2013) - Sutter, Peter; Sutter, Eli
Abstract The growth and properties of two‐dimensional (2D) materials–graphene as well as related monolayer systems, such as hexagonal boron nitride–on metals are topics of high scientific and technological interest. Real‐time low‐energy electron microscopy (LEEM) can provide unique insight into the fundamental growth mechanisms of 2D materials on metal substrates. In combination with in situ spectroscopic measurements, LEEM can greatly facilitate the search for synthesis and processing protocols that produce 2D materials with desired properties for applications. Here, progress is reviewed in understanding the scalable growth of high‐quality graphene on metals, novel processing strategies based on selective chemical reactions at the graphene/metal interface, and important materials properties (structure, electronic properties, work function, etc.) by surface microscopy and complementary methods, using graphene/ruthenium as a model system. The body of work shows that in situ microscopy can be used as a powerful tool for achieving and probing a wide range of functionalities in 2D materials.